Author, Text, and Writing: Roland Barthes and “The Death of the Author” (Journal of the College of Languages (JCL), 2023)
Roland Barthes’s essay “The Death of the Author” talks about the role of writers when they are creating content. I examined the meaning of Barthes’s essay, which advocates separating writers from their texts. Although the essay does not refer to the literal death of writers, it implies that distinguishing them from their texts can lead to an understanding of their content based on readers’ backgrounds and previous understandings. I concur with Barthes’s argument that if some readers attempt to understand writers, they might want to read the content from the writers’ perspective, which would limit the readers’ understanding of the texts. Therefore, for readers to fully grasp the meaning of a text, they must interpret the words based on their understanding and experiences, not from the authors’ point of view, because words have different meanings for people from different parts of the world.